African presidents. Cape Verde - Nascimbeni, Carlos; Martins, Franklin; Carlos Alberto Jr., Eduardo Poiano; Alberto Junior, Carlos; Poiano, Eduardo; Discovery Civilization (Television network); Cine Group (Firm); Utopic Documentaries (Firm) ([Brasilia, Brazil] : Cine Group, 2013)
An overview of the country of Cape Verde and an interview with president Jorge Carlos Fonseca.
Originally relaseased as a motion picture in 2013 in the Discovery Civilization Latin American TV channel.
Interview and reporting: Franklin Martins.
Cinematographers, Marco Romiti ; editors, Alex Tanin, Daniel Macacchero.
In Portuguese with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 28, 2021)
Keywords: Fonseca, Jorge Carlos, -- 1950-; Presidents -- Cabo Verde -- Interviews; Documentary television programs; Nonfiction television programs; Internet videos; Streaming video